Address of Rector Prof. dr. Zdravko Kačič on Rector’s Day at University of Maribor - Kačič, Zdravko (Acta Medico-Biotechnica, 2025)
Revered Guest Rectors and Vice-Rectors of Slovenian universities, Revered Academic Community of the University of Maribor: Prize Winners, Vice Rectors,Deans of Faculties, Emeritus Professors and Retired Professors, Teachers, Researchers and Associate Experts,Students, Ladies and Gentlemen!This year is a special Jubilee year for the University of Maribor. Fifty years ago, on September 18, 1975, “a second Slovenian university was solemnly proclaimed upon the sound of a fanfare in an assembly of distinguished guests and locals.” With today’s ceremony, we begin a year-long celebration to mark the 50th anniversary of the founding of the University of Maribor.